THE ARCS MOTIVATIONAL MODEL IMPLEMENTED BY ENGLISH TEACHERS IN TEACHING ENGLISH AS FOREIGN LANGUAGE AT SMAN 1 KOTA BENGKULU - Rossy Ananda Putri Lubis; Kasrawati (Teaching English and Language Learning English Journal, 2023)
The objective of this research was to investigate the implementation of the ARCS Motivational model in TEFL at SMAN 1 Kota Bengkulu. The design of this research was descriptive qualitative research. The subject of the study was all of the English teachers who teach English at SMAN 1 Kota Bengkulu. There were three English teachers who become the subject of this research. The researcher used observation checklist and interview to obtain the data. This research finding showed that there were 93% of attention indicator, 84% of relevance indicator, 53% of confidence indicator, and 67% of satisfaction indicator implemented by English teachers as ARCS Model in teaching English Foreign Language at SMAN 1 Kota Bengkulu. Attention indicator of ARCS models dominantly implemented by the teachers with percentage 93%. It was suggested for English teachers to implement more the confidence indicator since all of indicators of ARCS models is important to improve and encourage the students’ motivation in learning English. For further research, it will be better if other researchers can continue this research by conducting other design of research, such as; quasi experimental research or action research related to the implementation of ARCS models in teaching English at SMAN 1 Kota Bengkulu. Keywords: : ARCS Motivational Model, Teaching English as Foreign Language